Yearbook of the International Law Commission 2014, Vol. II, Part 1 - UN ILC (United Nations, 2020)
The Yearbook contains the official records of the Commission and is an indispensable tool for the preservation of the legislative history of the documents emanating from the Commission, as well as for the teaching, study, dissemination and wider appreciation of the efforts undertaken by the Commission in the progressive development of international law and its codification. Volume II (Part One) reproduces the edited versions of the official documents considered by the Commission at the respective annual session.